Impact of grassland saline-alkaline degradation on domestic herbivore rumen microbiota and methane emissions - Wang, Yizhen; Jiang, Xin; Ma, Guangming; Sun, Youran; Wang, Xue; Sun, Haixia; Li, Yanan; Wang, Ling (Frontiers in Veterinary Science, 2025)
IntroductionGrazing ruminant production has the risk of degrading the environment beyond natural recovery due to their production of enteric methane (CH4) which is the main contributor to the increase in global CH4 emissions. In particular, grasslands are currently experiencing severe saline-alkaline degradation that is prevalent in arid and semi-arid grassland areas globally. Yet, the impact of grassland saline-alkaline degradation-induced alterations in plant resources on herbivore, and subsequent CH4 emissions, remain underexplored.MethodsHere we examined these effects by feeding domestic ruminant-sheep with plants from undegraded (UG), moderately degraded (MG), and severely degraded grasslands (SG), focusing on rumen key microbes and nutrition process.ResultsOur results showed that moderately and severely saline-alkaline degradation of grasslands differently influences rumen key microbes associated with CH4 synthesis, thereby affecting CH4 emissions of ruminants. Specifically, the relative abundance of Treproema that can competitively inhibit the CH4 production was significantly increased in MG-fed sheep, which resulted in reduced CH4 emissions. Conversely, the relative abundance of Methanosphaera that positively related to CH4 production was significantly increased in SG-fed sheep, which resulted in increased CH4 emissions. Forage resources in severely degraded grasslands exhibited extremely high sodium (Na) content, while high forage diversity was found in moderately degraded grassland. Further, we found that increased Na intake has a significant influence on the abundance of Methanosphaera.DiscussionTaken together, our study provides novel insights into the underlying mechanism of the CH4 emissions induced by saline-alkaline degradation in ruminant herbivores; the increase in Na intake induced by grassland saline-alkaline degradation could be an important factor affecting rumen Methanosphaera thereby CH4 emissions by livestock. Our findings suggest that increasing grassland saline-alkaline degradation worldwide will greatly change the risk of CH4 emissions from grazing ruminants depending on the degree of degradation, which should be incorporated into future consideration of grassland carbon budgets.